Seeds of collapse? Reconstructing the ancient agricultural economy at Shivta in the Negev. (15th September 2016) - Fuks, Daniel; Weiss, Ehud; Tepper, Yotam; Bar-Oz, Guy
Abstract : Lessons from history on sustainability, collapse and resilience are the ultimate goal of the Byzantine Bio-Archaeology Research Program of the Negev (BYBAN) (Tepper et al. 2015 ). Addressing the unprecedented flourishing and collapse of the Byzantine Negev agricultural settlements (fourth–seventh centuries AD), the BYBAN project offers a unique and original approach. It focuses on ancient middens and domestic contexts, which provide an exceptional focus on the materiality of daily life. Archaeobotanical research is central to this project because the copious plant remains retrieved are a reflection of the region's agricultural economy and its environmental sustainability. This approach will enable us to answer important research questions about the Byzantine–Islamic transition in the Negev: what were the major cash and subsistence crops? Which were grown locally, and which, if any, were imported? How, if at all, did the agricultural economy change during the Byzantine–Islamic transition? Were there any major changes in climatic conditions, and, if so, can they be implicated as a cause for agricultural collapse?